The inhibition of the highly expressed miR-221 and miR-222 impairs the growth of prostate carcinoma xenografts in mice. - Neri Mercatelli (Public Library of Science (PLoS), 2008)
Background MiR-221 and miR-222 are two highly homologous microRNAs whose upregulation has been recently described in several types of human tumors, for some of which their oncogenic role was explained by the discovery of their target p27, a key cell cycle regulator. We previously showed this regulatory relationship in prostate carcinoma cell lines in vitro, underlying the role of miR-221/222 as inducers of proliferation and tumorigenicity. Methodology/principal findings Here we describe a number of in vivo approaches confirming our previous data. The ectopic overexpression of miR-221 is able, per se, to confer a high growth advantage to LNCaP-derived tumors in SCID mice. Consistently, the anti-miR-221/222 antagomir treatment of established subcutaneous tumors derived from the highly aggressive PC3 cell line, naturally expressing high levels of miR-221/222, reduces tumor growth by increasing intratumoral p27 amount; this effect is long lasting, as it is detectable as long as 25 days after the treatment. Furthermore, we provide evidence in favour of a clinical relevance of the role of miR-221/222 in prostate carcinoma, by showing their general upregulation in patient-derived primary cell lines, where we find a significant inverse correlation with p27 expression. Conclusions/significance These findings suggest that modulating miR-221/222 levels may have a therapeutic potential in prostate carcinoma.